Tax advisors and tax fraud: keys to understanding their authorship and participation in spanish criminal law - Cevallos Altamirano, Andrés (2023)
This article analyzes the legal nature of the crime of tax fraud in Spain. It is discussed whether it is a special, proper or mixed crime, as this limits the criminal liability. Regarding authorship and participation, the criminal liability of the tax advisor is analyzed in different scenarios in which the advisor may be involved in unlawful acts. It discusses scenarios in which the tax advisor and the taxpayer jointly participate in the fraud, and considers whether the advisor acts as a co-perpetrator or necessary cooperator depending on his participation. Finally, criteria are offered for each of these forms of perpetration and participation.